STRATEGI BERTAHAN HIDUP NELAYAN BURUH DI DESA MESKOM KECAMATAN BENGKALIS KABUPATEN BENGKALIS PROVINSI RIAU - Kristianti Kristianti; Kusai Kusai; Lamun Bathara (Berkala Perikanan Terubuk, 2014)
This research was conducted in August 2013. The objectives of this studywere: 1) Determine the survival strategies run by fishermen laborers 2) Know thefishermen’s labor reason refained his job as a fisherman in the village MeskomBengkalis Bengkalis District of Riau Province. Respondents in this study were 21people living as fishermen by sensus method. Survival strategies undertaken byfishermen had seen from social and economic strategy. Social strategies, amongothers, Patron client relationship and Gathering (Arisan). Economic strategiesinclude households member to work, such as used children in work, jobdiversification such as farmer labour and labor market, Pressing expenditure andaccounts payable.Keywords: Survival Strategies, Social Strategy, Economic Strategy, Bengkalis